When Immunity Kills: The Lessons of SARS-CoV-2 Outbreak - Taoufik, Yassine; de Goër de Herve, Marie-Ghislaine; Corgnac, Stéphanie; Durrbach, Antoine; Mami-Chouaib, Fathia (Frontiers in Immunology, 2021)
Since its emergence at the end of 2019, SARS-CoV-2 has spread worldwide at a very rapid pace. While most infected individuals have an asymptomatic or mild disease, a minority, mainly the elderly, develop a severe disease that may lead to a fatal acute respiratory distress syndrome (ARDS). ARDS results from a highly inflammatory immunopathology process that includes systemic manifestations and massive alveolar damages that impair gas exchange. The present review summarizes our current knowledge in the rapidly evolving field of SARS-CoV-2 immunopathology, emphasizing the role of specific T-cell responses. Indeed, accumulating evidence suggest that while T-cell response directed against SARS-CoV-2 likely plays a crucial role in virus clearance, it may also participate in the immunopathology process that leads to ARDS.